The 5 is the coefficient...
Expression 1 is 25
6*7-3^2*9+4^3
First simplify all the exponents to get 6*7 - 9 * 9 + 64 and then multiply the two numbers to get 42 - 81 + 64 and just add = 25
For expression 2, if you put the parantheses around (5+4)*2+6-2*2-1, it'll be 19
(5+4)*2+6-2*2-1
9*2+6-2*2-1
18+6-4-1
24-5
19
Remember order of operations
Answer:14
Step-by-step explanation:
x+y=56
x:y=5:3
Sum of ratio=5+3
Sum of ratio=8
x=5/8x56
x=(5x56) ➗ 8
x=280 ➗ 8
x=35
y=3/8x56
y=(3x56) ➗ 8
y=168 ➗ 8
y=21
x-y
35-21=14
x-y=14
The basketball coach spent 80 dollars more than the baseball coach